(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
Basic literacy skills, including reading, writing, and arithmetic, are the main foundation for the learning success of primary school students. However, after the Covid-19 pandemic, some students in Indonesia, including those in Kupang City, still experience difficulties in mastering basic literacy due to learning loss. This study aims to analyse basic literacy clinical assistance strategies through the Lopo Pintar Programme as a community-based intervention model in supporting the recovery of primary school students’ literacy skills. The research method used is a narrative literature review by examining scientific articles, education policy reports, and relevant local government programme documents. The results of the study show that contextual, intensive, and collaborative clinical literacy assistance has proven effective in improving the reading and writing skills of primary school students. The involvement of teacher training students as learning assistants also plays an important role in creating an adaptive, interactive, and meaningful learning process for students. These findings confirm that community-based literacy interventions are a relevant and sustainable strategy for accelerating the recovery of students’ basic literacy skills after the Covid-19 pandemic.